Part I: Synthesis and characterization of titania and magnesium nanoparticles for hydrogen production and storage. Part II: Characterization and growth of branched silicon nanowires grown via a simultaneous vapor-liquid-solid and vapor-solid-solid mechanism - Shissler, Daniel Jay, author; Prieto, Amy, advisor; Shores, Matthew, committee member; Rappé, Anthony, committee member; Van Orden, Alan, committee member; Dandy, David, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.
Synthesis and characterization of titania and magnesium nanoparticles for hydrogen production and storage
Characterization and growth of branched silicon nanowires grown via a simultaneous vapor-liquid-solid and vapor-solid-solid mechanism
Keywords: photocatalysis; hydrogen storage; Si nanowires